2016
DOI: 10.1016/j.cjtee.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of alcohol and substance abuse among motorcycle drivers in Fars province, Iran

Abstract: PurposeThe aim of this present study is to investigate the prevalence of alcohol and substance abuse (ASA) and its relationship with other risky driving behaviors among motorcycle drivers.MethodsThis is a cross sectional study which is performed at Shiraz city of Iran. Data from motorcycle drivers were collected using a standard questionnaire in eight major streets at different times of the day. The data includes consumption of alcohol and other substances two hours before driving and some of the risky behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 38 publications
8
13
0
2
Order By: Relevance
“…Some studies have shown that single people adopt more risky behaviors (e.g., excessive speed and DUIA) than those who are married [18,50,51]. Similarly, this study found unmarried status to be a risk factor for DUIA in all Brazil and in the Central-West macroregion.…”
Section: Discussionsupporting
confidence: 73%
“…Some studies have shown that single people adopt more risky behaviors (e.g., excessive speed and DUIA) than those who are married [18,50,51]. Similarly, this study found unmarried status to be a risk factor for DUIA in all Brazil and in the Central-West macroregion.…”
Section: Discussionsupporting
confidence: 73%
“…Alcohol use was more frequent among those that were unmarried, separated, divorced or widowed when compared to those who were married. This is similar to another study that found that those who were not married were more likely to consume alcohol than those who were married (Heydaria, et al, 2016).…”
Section: Determinants Of Alcohol Use Among Road Traffic Injured Victimssupporting
confidence: 89%
“…In another study conducted in Australia, the researchers found that riders, passengers, and pedestrians were the most vulnerable victims (Cameron et al, 2005). Similarly, the findings of a study in China showed that motorcyclists, bicycle riders, and pedestrians were the most victims of traffic collisions (Qi, Yang, Qi, Zhang, & Wang, 2006 is notable that motorcycle collisions and their related injuries are major problems in developing countries (Heydari et al, 2016). In Iran and especially in Tehran, a large number of motorcyclists use their vehicles for transportation or earning money.…”
Section: Discussionmentioning
confidence: 94%